L-Theanine Extends the Lifespan of Caenorhabditis elegans by Reducing the End Products of Advanced Glycosylation - Zhihang Huang; Haiming Jing; Yan Pan; Hongxia Cai; Wenjing Zhang; Jingyuan Zhu; Nan Zhang; Dan Wu; Wentao Xu; Hexiang Qiu; Huihui Bao; Guojun Li; et al. (Foods)
L-theanine, a non-protein amino acid naturally occurring in tea leaves, is recognized for its antioxidant, anti-inflammatory, and neuroprotective properties. Despite its known benefits, the mechanisms by which L-theanine influences lifespan extension remain poorly understood. This study investigated the effects of L-theanine on the lifespan of Caenorhabditis elegans and explored the underlying mechanisms. Our findings indicate that L-theanine significantly diminishes the accumulation of advanced glycation end products (AGEs), which are biomarkers closely linked to aging and age-related diseases. Through an AGE-level analysis, we observed that L-theanine, when administered during early adulthood, notably extended the lifespan of Caenorhabditis elegans under both normal and high-glucose-induced stress conditions. L-theanine enhanced the lifespan under typical conditions and provided protective effects against high-glucose-induced stress. A further analysis demonstrated that L-theanine extends the lifespan of Caenorhabditis elegans by modulating the DAF-2/DAF-16 insulin-like signaling pathway and reducing the accumulation of advanced glycation end products (AGEs). In summary, this study identified L-theanine as a potential anti-aging intervention that extends the lifespan by reducing AGE accumulation and regulating insulin-like signaling pathways. These findings provide new insights for developing anti-aging strategies and lay the groundwork for further research on the potential benefits of L-theanine in mammals. Future studies could explore the molecular mechanisms, test L-theanine in mammalian models, and assess the long-term side effects.